Knock-in model of Dravet syndrome reveals a constitutive and conditional reduction in sodium current. - Schutte, R.J.; Schutte, S.S.; Algara, J.; Barragan, E.V.; Gilligan, J.; Staber, C.; Savva, Y.A.; Smith, M.A.; Reenan, R.; O'Dowd, D.K. (Journal of Neurophysiology, 2014)
Hundreds of mutations in the SCN1A sodium channel gene confer a wide spectrum of epileptic disorders, requiring efficient model systems to study cellular mechanisms and identify potential therapeutic targets. We recently demonstrated that Drosophila knock-in flies carrying the K1270T SCN1A mutation known to cause a form of genetic epilepsy with febrile seizures plus (GEFS+) exhibit a heat-induced increase in sodium current activity and seizure phenotype. To determine whether different SCN1A mutations cause distinct phenotypes in Drosophila as they do in humans, this study focuses on a knock-in line carrying a mutation that causes a more severe seizure disorder termed Dravet syndrome (DS). Introduction of the DS SCN1A mutation (S1231R) into the Drosophila sodium channel gene para results in flies that exhibit spontaneous and heat-induced seizures with distinct characteristics and lower onset temperature than the GEFS+ flies. Electrophysiological studies of GABAergic interneurons in the brains of adult DS flies reveal, for the first time in an in vivo model system, that a missense DS mutation causes a constitutive and conditional reduction in sodium current activity and repetitive firing. In addition, feeding with the serotonin precursor 5-HTP suppresses heat-induced seizures in DS but not GEFS+ flies. The distinct alterations of sodium currents in DS and GEFS+ GABAergic interneurons demonstrate that both loss- and gain-of-function alterations in sodium currents are capable of causing reduced repetitive firing and seizure phenotypes. The mutation-specific effects of 5-HTP on heat-induced seizures suggest the serotonin pathway as a potential therapeutic target for DS.